(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
The diffracted intensity from a phase depends on variety of factors such as structure factor, Lorentz polarization …etc. In this research the above mentioned factors have been calculated for both and . In addition, the ratio between diffracted intensities is has been determined with value , which corresponds to a depth 0.25mm from the studied steel sheet. The variation of diffracted intensity as a function of depth of surface sheet reveals a peak at 630 au at depth 0.4 mm which indicated to site of martinsite formation. Keywords: austenite phase, martinsite phase, diffracted intensity, structure factor, volume fraction.